The "little 3 with a square root" is a "cube root." It's similar to the square root, but it's for numbers that are "cubed" (for example, 2 * 2 * 2 is 2³, which is 8, where 2 is the "cube root" of 8.), whereas the square root is for numbers that are squared (2 * 2 = 2², which is 4, where 2 is the "square root" of 4). 1. ³√(3x - 1) = 2 To cancel this, raise both sides to the 3rd power. The radical and the power on the left side will disappear. 3x - 1 = 2³ 3x - 1 = 2 * 2 * 2 3x - 1 = 8 3x - 1 + 1 = 8 + 1 3x = 9 x = 3 Answer: x = 3 2) ⁴√(x - 7) = 2 Raise both sides to the power of 4. The radical and the power on the left side will disappear. x - 7 = 2⁴ x - 7 = 2 * 2 * 2 * 2 x - 7 = 16 x - 7 + 7 = 16 + 7 x = 23 Answer: x = 23 3) x² - 6x - 8 = 0 This is in the form ax² + bx + c = 0 Find factors of 'c' that add up to 'b', and set them in this format (x + F1)(x + F2) = 0, where F1 and F2 are the two factors of 'c'. Since F1 = -2 and F2 = -4, (x - 2)(x - 4) = 0 Answer: (x - 2)(x - 4) = 0